Rapid clinical mutational testing of KRAS, BRAF and EGFR: a prospective comparative analysis of the Idylla technique with high-throughput next-generation sequencing. Issue 1 (11th July 2019) - Van Haele, Matthias; Vander Borght, Sara; Ceulemans, An; Wieërs, Michiel; Metsu, Sofie; Sagaert, Xavier; Weynand, Birgit
Abstract : Aims: Precision medicine therapy is remodelling the diagnostic landscape of cancer. The success of these new therapies is often based on the presence or absence of a specific mutation in a tumour. The Idylla platform is designed to determine the mutational status of a tumour as quickly and accurately as possible, as a rapid, accurate diagnosis is of the utmost importance for the treatment of patients. This is the first complete prospective study to investigate the robustness of the Idylla platform for EGFR, KRAS and BRAF mutations in non-small cell lung cancer, metastatic colorectal cancer and metastatic melanoma, respectively. Methods: We compared prospectively the Idylla platform with the results we obtained from parallel high-throughput next-generation sequencing, which is the current gold standard for mutational testing. Furthermore, we evaluated the benefits and disadvantages of the Idylla platform in clinical practice. Additionally, we reviewed all the published Idylla performance articles. Results: There was an overall agreement of 100%, 94% and 94% between the next-generation panel and the Idylla BRAF, KRAS and EGFR mutation test. Two interesting discordant findings among 48 cases were observed and will be discussed together with the advantages and shortcoming of both techniques. Conclusion: Our observations demonstrate that the Idylla cartridge for the EGFR, KRAS and BRAF mutations is highly accurate, rapid and has a limited hands-on time compared with next-generation sequencing.